Thermal treatment effects on phase transitions in P(VDF-TrFE) - Alves, Neri [UNESP]; Ruiz, Paulo R O [UNESP]; Job, Aldo E. [UNESP]; Oliveira, O. N. [UNESP]; Giacometti, Jose A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1999)
Differential scanning calorimetry (DSC) studies were performed for 60/40 P(VDF-TrFE). The results not only confirm the importance of thermal history but also show that the samples with various configurations in terms of ferroelectric phases can be obtained via thermal treatment.
Keywords: Calorimeters; Crystal structure; Differential scanning calorimetry; Ethylene; Heat treatment; Melting; Nitrogen; Thermal effects; Ferroelectric phases; Polyvinylidene fluoride; Trifluorethylene; Fluorine containing polymers